A U-shaped non-linear association between serum uric acid levels and the risk of Hashimoto’s thyroiditis: a cross-sectional study - Yan, Manli; Shi, Wenhua; Gong, Ping; Xie, Yunsi; Zhang, Kaiyuan; Li, Xiang; Wei, Hua (Frontiers in Endocrinology, 2025)
ObjectivePrevious studies have found that the relationship between metabolic indicators and Hashimoto’s thyroiditis (HT) in non-diabetic adults remains unclear. This study aims to explore the association between metabolic indicators and HT, providing new theoretical insights for the clinical management of HT.MethodsClinical data were collected from 2,015 non-diabetic adults at Guangdong Provincial Hospital of Chinese Medicine. The relationship between metabolic indicators and HT was analyzed using SPSS 26.0, R (version 4.2.1), and Zstats.ResultsAmong the 2,015 non-diabetic adult participants included in the study, 1,877 were in the non-HT group, while 138 were in the HT group. Significant differences were observed in metabolic indicators, including serum uric acid (SUA), serum creatinine (SCr), albumin (ALB) and high-density lipoprotein cholesterol (HDL-C), between the two groups, with statistical significance. A binary logistic regression model was established, revealing that SCr had a significant impact in both univariate and multivariate analyses. To further investigate the relationship between metabolic indicators and HT, we conducted a restricted cubic spline (RCS) analysis. The results demonstrated a clear non-linear relationship between SUA and HT, both before and after adjustment (All P < 0.01). Therefore, based on the inflection points derived from the RCS analysis, a segmented logistic regression analysis was performed. The findings indicated a significant association between both low and high levels of SUA and HT (Lower OR: 2.043; 95% CI: 1.405-3.019; P < 0.001; Higher OR: 2.369; 95% CI: 0.998-4.999; P = 0.034).ConclusionThis study is the first to reveal a U-shaped association between SUA levels and the risk of HT, suggesting that maintaining SUA levels within the range of 359.0-540.0 μmol/L may help reduce the risk of HT occurrence. This finding provides a new perspective for early intervention and long-term management of HT, particularly in terms of SUA regulation in HT patients, which holds potential clinical value.